The patient perspective on remote monitoring of patients with an implantable cardioverter defibrillator: Narrative review and future directions. Issue 7 (30th June 2017) - Timmermans, Ivy; Meine, Matias; Zitron, Edgar; Widdershoven, Jos; Kimman, Geert; Prevot, Sébastien; Rauwolf, Thomas; Anselme, Frédéric; Szendey, Istvan; Romero Roldán, Javier; Mabo, Philippe; Schaer, Beat; et al.
Abstract: Background: Studies have shown that remote patient monitoring (RPM) of implantable cardioverter defibrillators (ICDs) is at least comparable to in‐clinic follow‐up with regard to clinical outcomes and might be cost‐effective, yet RPM is not standard clinical practice within Europe. Better insight into the patient perspective on RPM may aid in its acceptance, implementation, and reimbursement. This narrative review (1) summarizes existing evidence on the impact of RPM on patient‐reported outcomes and (2) discusses future directions in examining the patient perspective. Methods and Results: Literature review indicated that only five randomized trials on RPM in ICD patients included patient‐reported outcomes, with inconclusive results. Observational studies show a trend toward good patient satisfaction and acceptation of RPM. Yet, results should be interpreted with caution due to a number of limitations including a potential selection bias, use of generic/nonvalidated questionnaires, relatively short follow‐up durations, and a lack of subgroup identification. Conclusion: Although RPM seems to be safe, effective, timely, and efficient, the patient perspective has received little attention so far. The scarce evidence on patient‐reported outcomes in RPM studies seems to be positive, but future trials with a follow‐up of ≥12 months and validated patient‐reported outcome measures are needed. The REMOTE‐CIED study from our group is the first prospective randomized controlled trial primarily designed to examine the patient perspective on RPM, and is powered to identify characteristics associated with RPM satisfaction and benefit. Results are expected in 2018 and will add valuable information to the current evidence.